PERENCANAAN STRATEGI PEMASARAN USAHA BENGKEL BARU (STUDI KASUS DI INTI MOTOR PONOROGO) - Stephanie Kusumo; Rosita Meitha Surjani; Esti Dwi Rinawiyanti (CALYPTRA, 2013)
The addition of the motorcycle population is increasing every year. The density of activity in the streets is demanding comfort, so the vehicle should be always in good condition. Therefore it’s required that the user do service for motorcycle routinely. INTI MOTOR was established by Mr David Hartanto on December 29, 2011 in Jl. K.H. Ahmad Dahlan No. 25 Ponorogo. INTI MOTOR is a business unit that sells a variety of motorcycle spare parts and variations, as well as serving motorcycle repair service, oil change, replace accu etc. The uniqueness of this workshop which distinguishes it from other workshop is a specialist cleaning services polished motorcycle. For this time being, INTI MOTOR is the first workshop in Ponorgo that provides cleaning polishing. However, this superiority couldn’t attack costumer. That’s why INTI MOTOR should take proper planning and marketing strategies in order to be more effectively introducing and stimulating consumer interest towards this superior service which still new in the town of Ponorogo. Currently as a new business workshop, this workshop’s sale has not still reached the BEP and difficult to gain a profit. So it’s necessary that INTI MOTOR has a marketing planning strategies in order to reach BEP quickly. The study was conducted by distributing questionnaire to the group of respondents actual consumers and potential consumers. The results of the questionnaire was used to plan marketing strategies including STPD: Segmentation based on demographic aspects, the Targetting is the INTI MOTOR’s consumers who have motorcycle, men between 16-35 years old, family status, the occupation is self-employed, with an average expenditure among <Rp 1,000,000 to Rp 1,999,999 per month, the Positioning is to build the image with the tagline that could represent INTI MOTOR “harga terjangkau service memuaskan". INTI MOTOR’s Differentiation is product differentiation which is a specialist cleaning polishing motorcycle. Proposed differentiation is programs and tools to perform injection engine service, tire opener, and motorcycle lifts. Other marketing strategies are 8P marketing mix which include Elements Product, Place and Time, Price and Other User Outlays, Promotion and Education, Process, Physical Environment / Evident, People, and Productivity and Quality, the total cost of application of the entire strategy is Rp 27.955.925.